The Impact of Campus Facilities and Lecturer Services on Student Satisfaction in Higher Education - Ismail, Ahmad Nur; Pupita, Dara; Daniel, Dellyma Fajri (MultiTech Publisher, 2024)
Education is the foundation of a nation. Universities have an important role in educating the nation's life and are responsible for the progress of a nation. To achieve good quality education, a lot of involvement from various parties is needed. Apart from that, adequate infrastructure and educators in universities need to be considered. This research is motivated by the importance of lecturer facilities and services at the STKIP PGRI Ponorogo campus. The aim of this research is to determine the influence of campus facilities and lecturer services on student satisfaction at STKIP PGRI Ponorogo. This research uses a quantitative approach with descriptive methods. The objects of this research are all STKIP PGRI Ponorogo students. Based on the Anova table, it is shown that the value of Fcal is greater than that of Ftable, which is 33,536>3,168, then H1 is accepted. Meanwhile, the results of the determination coefficient (R2) show that the contribution of variable X can explain the variable Y. Thus, it can be concluded that student satisfaction (Y) can be influenced by campus facilities and lecturer services (X) by only 55%. The remaining 45% is influenced by other variables that are not included in this study. After being analyzed using multiple linear regression, it can be concluded that student satisfaction is influenced by campus facilities and lecturer services.